Capillary hemangioma oral cavity: Report of two cases - NAMDAR PEKİNER, FİLİZ MEDİHA; KESER, GAYE (My University, 2023)
Capillary Haemangioma is a benign vascular tumor that is characterized by blood vessel growth and is usually known to be a developing hamartomatous disease of infancy and childhood. The current case report describes an exceptionally unusual atypical appearance of capillary haemangioma. These lesions confront the doctor with a diagnostic quandary and, if not appropriately controlled, can lead to significant problems.
Keywords: oral hemangioma; oral mucosa; gingiva